The correlation between self regulated and learning achievement of underachiever students - Syahniar Syahniar (International Conferences on Educational, Social Sciences and Technology)
This research is conducted based on the fact that underachiever students are still found in the field students whose intelligence is high but their learning outcomes are below standard. Self regulated is assumed as a factor exerting an influence upon underachiever students’ learning achievement. The aim of this research is to see the correlation between self regulated and learning achievement of the underachievers. This research is classified into quantitative study which was conducted by applying correlational method. The subjects of the research were 87 students. The instruments used is self regulated instruments by applying scale of Likert model. The data obtained were analyzed by using simple regression. The results of the research indicate that there is a positive and significant correlation between self regulated and learning achievement of the underachievers.